Can participatory processes lead to changes in the configuration of local mental health networks? A social network analysis - Camacho, Salvador; Hilber, Adriane Martin; Ospina-Pinillos, Laura; Sánchez-Nítola, Mónica; Shambo-Rodríguez, Débora L.; Lee, Grace Yeeun; Occhipinti, Jo-An (Frontiers in Public Health, 2023)
Systems modeling offers a valuable tool to support strategic decision-making for complex problems because it considers the causal inter-relationships that drive population health outcomes. This tool can be used to simulate policies and initiatives to determine which combinations are likely to deliver the greatest impacts and returns on investment. Systems modeling benefits from participatory approaches where a multidisciplinary stakeholder group actively engages in mapping and contextualizing causal mechanisms driving complex system behaviors. Such approaches can have significant advantages, including that they may improve connection and coordination of the network of stakeholders operating across the system; however, these are often observed in practice as colloquial anecdotes and seldom formally assessed. We used a basic social network analysis to explore the impact on the configuration of the network of mental health providers, decision-makers, and other stakeholders in Bogota, Colombia active in a series of three workshops throughout 2021 and 2022. Overall, our analysis suggests that the participatory process of the systems dynamics exercise impacts the social network’s structure, relationships, and dynamics.